Actualization of a unified approach to the assessment of injuries in martial arts in the aspect of theoretical analysis of sports practice in Iran - Baniasadi E.; Salamatov M.B.; Salamatova K.G. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to actualize the problem of injuries in martial arts and develop a unified approach to systematizing sports injuries and assessing their severity based on the analysis of Iranian scientific literature. Methods and structure of the study. The work used the method of content analysis of scientific sources published from 2003 to the present, which were conducted in the field of studying the prevalence of injuries or risk factors for injury in Iranian martial artists. In this study, related articles were searched using keywords and specialized databases such as Google Scholar, Sciencedirect, PubMed, SID, Magiran and Irandoc. Results and conclusions. It has been established that there are actual differences in approaches and methods for assessing the severity of injuries and the localization of these injuries in sports practice in different countries. One of the distinctive reasons is that there are no strict standards and unified methods for determining injury in the sports listed above. Another reason is the obvious differences in the use of terminology to refer to and explain types of injuries, which makes it difficult to generalize the results because the terms and words are not identical. The authors conclude that the development of a unified approach to assessing injuries and ways to prevent them in martial arts will help achieve a high level of competence of coaches in teaching athletes technical techniques and will reduce the degree of injuries in martial arts.